2020
DOI: 10.3390/ijerph17207697
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Habits, Shift Work, and the Metabolic Syndrome: The Korea Nurses’ Health Study

Abstract: Metabolic syndrome (MetS) is an important public health problem, and unhealthy dietary habits and shift work are considered major factors that increase the prevalence of MetS. The purpose of this study was to examine whether dietary habits, alcohol drinking, and shift-working were associated with development of MetS in shift-working female nurses. This study analyzed cross-sectional survey data from the Korea Nurses’ Health Study (KNHS). Of the 1638 nurses, 403 participants were selected based on the propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 59 publications
0
28
0
1
Order By: Relevance
“…The works by Jung et al [17] and Kim et al [40] have already observed that night work increases the incidence of appetite disorders and impacts physical and psychological wellbeing. Furthermore, it has also been established [41] that there are different dimensions of eating behaviour that are related to emotional eating, and this is associated with a deficit in impulse control [42], characteristic of uncontrolled eating and the ED subtype BN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The works by Jung et al [17] and Kim et al [40] have already observed that night work increases the incidence of appetite disorders and impacts physical and psychological wellbeing. Furthermore, it has also been established [41] that there are different dimensions of eating behaviour that are related to emotional eating, and this is associated with a deficit in impulse control [42], characteristic of uncontrolled eating and the ED subtype BN.…”
Section: Discussionmentioning
confidence: 99%
“…The MD, i.e., a diet rich in vegetables, fruits, greens, nuts and cereals, with low or moderate consumption of dairy products (yogurt, cheese) and poultry meat (mainly chicken) and limited consumption of red meat, sweets and bakery products, is one of the healthiest dietary patterns to follow, since it has been observed that health habits and lifestyle habits are intimately linked [13,17]. Higher adherence to the MD is associated with a lower risk of mortality, cardiovascular disease, cancer incidence, Parkinson's disease and Alzheimer's disease [17][18][19]. Adherence to the MD has been shown to be moderately low, even in Mediterranean countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Grand View Research reports [12], the market of these products is constantly growing. Moreover, these products are widely and easily available to consumers regardless of their age, gender and place of residence [13][14][15]. Carbonated drinks also meet the assumptions of global products, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…, tendo como resultado o índice de prevalência de 10,8%. Por fim,Jung et al (2020) encontraram insólitos 5,6% de acometimento pela síndrome em pesquisa transversal do Korea Nurses Health Study, realizada com 1.638 enfermeiros.…”
unclassified